2010
DOI: 10.1159/000306645
|View full text |Cite
|
Sign up to set email alerts
|

Association of Platelet and Leukocyte Counts with Delayed Cerebral Ischemia in Aneurysmal Subarachnoid Hemorrhage

Abstract: Background and Purpose: A proinflammatory prothrombotic state may increase the risk of delayed cerebral ischemia (DCI) after aneurysmal subarachnoid hemorrhage (SAH). We studied the relationship of levels of leukocytes, platelets, C-reactive protein (CRP), and erythrocyte sedimentation rate (ESR) with the development of DCI and with clinical outcome in patients with aneurysmal SAH. Methods: In 125 patients admitted within 72 h after aneurysmal SAH, we dichotomized initial blood levels at their median values an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(41 citation statements)
references
References 36 publications
2
36
1
2
Order By: Relevance
“…No relationship has been revealed between WBC count and rebleeding previous to our study, although high level of leukocyte count was reported to be associated with an increased risk of delayed cerebral ischemia after aSAH (15). It has also been shown that in mice, leukocytes and platelets adhere the microvasculature at the cerebral surface immediately after SAH.This may rapidly cause a whole-brain injury due to early inflammatory and prothrombogenic responses (12).…”
Section: Subgroup Analysis Of Aneurysm Locationmentioning
confidence: 46%
“…No relationship has been revealed between WBC count and rebleeding previous to our study, although high level of leukocyte count was reported to be associated with an increased risk of delayed cerebral ischemia after aSAH (15). It has also been shown that in mice, leukocytes and platelets adhere the microvasculature at the cerebral surface immediately after SAH.This may rapidly cause a whole-brain injury due to early inflammatory and prothrombogenic responses (12).…”
Section: Subgroup Analysis Of Aneurysm Locationmentioning
confidence: 46%
“…Other parameters of systemic inflammation like CRP en leukocytes may be more valuable predictors for DCI and poor outcome after SAH. One study found an increase in both CRP and leukocyte counts during the development of DCI which were significantly larger than in patients without DCI at the same period after onset of aneurysmal SAH, although neither CRP or leukocyte counts were found to be independent prognostic markers for the development of DCI or poor outcome [19]. Other studies also found an increase in leukocyte counts before or at the time of clinical manifestation of DCI [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Although systemic inflammatory reactions after SAH have been described earlier [18,35], the concept of…”
Section: Discussionmentioning
confidence: 99%